2013
DOI: 10.1520/acem20120030
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of the Accelerated Mortar Bar Test for Alkali-Silica Reactivity of Recycled Concrete Aggregates

Abstract: Using recycled concrete aggregate (RCA) as a replacement for natural aggregate in new concrete is a promising way to increase the overall sustainability of new concrete. This has been hindered, however, by a general perception that RCA is a sub-standard material because of the lack of technical guidance, specifically related to long-term durability, on incorporating RCA into new concrete. The goal of this research was to determine whether current testing methods (namely, ASTM C1260) for assessing natural aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Adams et al [ 68 ] considered that aggregate washing, used in NA AMBT and CPT tests, can reduce adhered cement paste in the RA, promote the hydration of anhydrous cement particles in RA, and/or leach calcium or alkalis from aggregates and adhered paste. The authors proposed limited washing at time intervals for each of the size fractions.…”
Section: Asr In Concrete With Potential Reactive Ramentioning
confidence: 99%
See 1 more Smart Citation
“…Adams et al [ 68 ] considered that aggregate washing, used in NA AMBT and CPT tests, can reduce adhered cement paste in the RA, promote the hydration of anhydrous cement particles in RA, and/or leach calcium or alkalis from aggregates and adhered paste. The authors proposed limited washing at time intervals for each of the size fractions.…”
Section: Asr In Concrete With Potential Reactive Ramentioning
confidence: 99%
“…Adams et al [ 68 ] also modified the mixing process because of the water absorption of RA. First they immersed the RA in water for 30 min and reached 85% of RA saturation.…”
Section: Asr In Concrete With Potential Reactive Ramentioning
confidence: 99%
“…The gradation of aggregate required for use in the ASTM C1567 test may be too small for this test method to work. Previous work has shown that the amount of crushing performed on an RCA can affect its reactivity (Shehata, Christidis et al, 2010;Adams, Ideker et al, 2012). This was attributed to the amount of adhered mortar on the aggregate (Shehata, Christidis et al, 2010;Adams, Ideker et al, 2012), which is reduced as the level of crushing is increased (Nagataki, Gokce et al, 2004).…”
Section: Mitigation Studymentioning
confidence: 99%
“…Research into the mechanical properties of concrete containing RCA has shown that, by limiting the amount of RCA used as replacement material in a given mixture and through proper design of a concrete mixture, similar or better concrete than that which is made with natural aggregates can be produced (SagoeCrentsil, Brown et al, 2001;Fathifazl, Abbas et al, 2009;Kou, Poon et al, 2011). RCA that is produced from parent concrete that has shown deterioration due to ASR has shown to be reactive when incorporated into new concrete (Gress, 2000;Shayan and Xu, 2003;Scott and Gress, 2004;Li and Gress, 2006;Gress, Snyder et al, 2009;Shehata, Christidis et al, 2010;Adams, Ideker et al, 2012). ASR is one of the most prevalent causes of premature concrete deterioration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation